1992
DOI: 10.1038/bjc.1992.181
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of collateral sensitivity to fluorouracil of a cis-diamminedichloroplatinum(II)-resistant human non-small lung cancer cell line

Abstract: A cisplatin(CDDP)-resistant subline of a human lung cancer cell line, PC-7/CDDP, was 4.7-fold more resistant to CDDP than the parent line in a colony-forming assay. The sensitivity of this cell line to anthracyclines, vinca-alkaloid, etoposide, mitomycin C, and bleomycin was similar to that of the parental line, PC-7. However, PC-7/CDDP exhibited 4-fold higher sensitivity to fluorouracil (FUra). Possible mechanisms associated with the collateral sensitivity to FUra were studied in PC-7/CDDP cells. The sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The first is a lack of synergism between the cytotoxic agents, despite preclinical and clinical studies (17) 4 (3) that demonstrate synergism between UFT® and cisplatin [31,32], A second possibility is that the modulation ofUFT® by leucovorin does not work in patients with NSCLC. Ac tually, whether the combination of cisplatin and fluoropyrimidines modulated with leucovorin is active for the treatment of NSCLC remains undefined, and in vitro studies show contradictory results [30,33], Sugimoto et al [33] observed that inhibition of thymidylate synthase after 5-FU treatment did not correlate with the DNAdirected activity of 5-FU. If Sugimoto's in vitro results correlate well with clinical activity, therapy with 5-FU modulated with leucovorin might not be useful for the treatment of NSCLC [33], However, the combination of cisplatin/5-FU/leucovorin achieved a 41% response rate in one trial [14], Finally, dose reduction may be one cause of the low response to this regimen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is a lack of synergism between the cytotoxic agents, despite preclinical and clinical studies (17) 4 (3) that demonstrate synergism between UFT® and cisplatin [31,32], A second possibility is that the modulation ofUFT® by leucovorin does not work in patients with NSCLC. Ac tually, whether the combination of cisplatin and fluoropyrimidines modulated with leucovorin is active for the treatment of NSCLC remains undefined, and in vitro studies show contradictory results [30,33], Sugimoto et al [33] observed that inhibition of thymidylate synthase after 5-FU treatment did not correlate with the DNAdirected activity of 5-FU. If Sugimoto's in vitro results correlate well with clinical activity, therapy with 5-FU modulated with leucovorin might not be useful for the treatment of NSCLC [33], However, the combination of cisplatin/5-FU/leucovorin achieved a 41% response rate in one trial [14], Finally, dose reduction may be one cause of the low response to this regimen.…”
Section: Resultsmentioning
confidence: 99%
“…Ac tually, whether the combination of cisplatin and fluoropyrimidines modulated with leucovorin is active for the treatment of NSCLC remains undefined, and in vitro studies show contradictory results [30,33], Sugimoto et al [33] observed that inhibition of thymidylate synthase after 5-FU treatment did not correlate with the DNAdirected activity of 5-FU. If Sugimoto's in vitro results correlate well with clinical activity, therapy with 5-FU modulated with leucovorin might not be useful for the treatment of NSCLC [33], However, the combination of cisplatin/5-FU/leucovorin achieved a 41% response rate in one trial [14], Finally, dose reduction may be one cause of the low response to this regimen. In fact, the response rate in patients receiving full doses was 25%, which is similar to that seen by other investigators with cisplatin/5-FU/leucovorin [34,35], Whatever the reasons, the results achieved with our regimen do not allow us to recommend its further study in the treatment of advanced NSCLC.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the efficacy of ELF, we added cisplatin because it is one of the most active agents in gastric cancer [9,10] and because it works synergistically with folinic acid/ 5-fluorouracil (5-FU) [11,12] and with etoposide [13] in experi mental tumors. Furthermore, there is a lack of cross resistance between these agents in vitro [14,15] and in vivo [16], Based on this background, we investigated in a phase I study the recommended dose of cisplatin ]P) that can be adminis tered together with a slightly modified ELF regimen. In this study.…”
Section: Introductionmentioning
confidence: 99%